Biofilm production under different atmospheres and growth media by Streptococcus agalactiae isolated from milk of cows with subclinical mastitis - Bonsaglia, Erika C. R. [UNESP]; Latosinski, Giulia S. [UNESP]; Rossi, Rodolfo S. [UNESP]; Rossi, Bruna F. [UNESP]; Possebon, Fábio S. [UNESP]; Pantoja, José Carlos F. [UNESP]; Fernandes Júnior, Ary [UNESP]; Rall, Vera L. M. [UNESP] (Springer Nature, 2019)
Different methods to analyze Streptococcus agalactiae biofilm formation have been investigated, but standardized protocols have not been developed. We compared S. agalactiae biofilm production among different atmospheres and growth media. Biofilm formation was studied in 32 isolates from bovine mastitis cases grown in Tryptone Soy Broth (TSB), Todd Hewitt Broth (THB), Luria Bertani Broth (LB) and Brain Heart Infusion (BHI), under two atmospheres, aerobic and 5% CO2. Regardless of the culture medium, growth under 5% CO2 resulted in a greater proportion of biofilm formation (65.63%), as compared with aerobic conditions (39.84%). Regardless of the atmosphere, the chances of biofilm formation were greater for isolates grown in TSB, as compared with THB [Odds ratio (OR) = 3.02], BHI (OR = 4.57), or LB (OR = 10.20). Thus, we suggest the use of 5% CO2 atmosphere and TSB in biofilm formation assays by Group-B streptococci (GBS) isolated from intramammary infections.
Keywords: Biofilm; Bovine mastitis; Milk; Streptococcus agalactiae; Tryptone soy broth